Penggunaan Pasir Yang Mengandung Zirkon Dan Batu Limbah Tambang Emas Dari Desa Hanua Sebagai Agregat Pada Campuran Hot Rolled Sheet Base (Hrs-Base) - Robby Robby; Supiyan Supiyan; Salonten Salonten (Fakultas Teknik, 2023)
AbstractNatural sand is sand obtained directly from nature and can be used directly as construction material without the need for processing first. While zircon sand is sand that is produced from the first pan process from gold mining and is often used by every activity in the production of ceramics, frit, metal casting, and refractory bricks. Based on this potential, efforts need to be made to utilize zircon sand from Hanua village as a construction material for a mixture of aggregate substitutes combined with natural sand as fine aggregate. The coarse aggregate used is gold mining waste stone from Hanua village. One of the environmental problems in Central Kalimantan is gravel waste resulting from gold mining production. Therefore, it is necessary to make efforts to utilize the gravel waste from the Hanua village. Therefore, this study tries to examine the effect of sand containing zircon and gold mine waste gravel on the asphalt mixture. This study aims to analyze the physical properties, marshall characteristics, and the optimum value of the Lataston Lapis Foundation mixture of HRS-Base (Hot Rolled Sheet -Base) type. Based on the calculation results, it was obtained that KAO of 7.3% obtained a Stability value of 925.00 kg, Flow of 3.25 mm, Cavity Between Aggregates of 23.48%, Air voids in Mixture of 4.60%, Cavity Filled with Asphalt of 77 ,95%, Marshall quotient of 300.00 kg/mm.Keywords : Hot Rolled Sheet - Base (HRS-Base), zirkon sand, gravel waste, Marshall ParameterAbstrakPasir alami adalah pasir yang diperoleh langsung dari alam dan langsung dapat digunakan sebagai bahan konstruksi tanpa perlu pengolahan terlebih dahulu. Sedangkan pasir zirkon adalah pasir yang dihasilkan dari proses dulang terlebih dahulu dari hasil penambangan emas dan sering digunakan oleh setiap kegiatan produksi keramik, frit, pengecoran logam, dan bata tahan api. Berdasarkan dari potensi tersebut perlu adanya upaya untuk memanfaatkan pasir zirkon dari desa Hanua sebagai bahan kontruksi campuran pengganti agregat yang digabungkan dengan pasir alami sebagai agregat halus. Untuk agregat kasar yang digunakan adalah batu limbah tambang emas dari desa Hanua. Salah satu permasalahan lingkungan di Kalimantan Tengah yaitu limbah kerikil hasil dari produksi tambang emas. Oleh sebab itu perlu adanya upaya untuk memanfaatkan limbah kerikil dari desa Hanua tersebut. Karena itu maka penelitian ini mencoba untuk meneliti pengaruh pasir yang mengandung zirkon dan batu kerikil limbah tambang emas pada campuran aspal. Penelitian ini bertujuan untuk menganilisis sifat-sifat fisik, karakterisitik marshall, dan nilai optimum pada campuran Lataston Lapis Pondasi jenis HRS-Base (Hot Rolled Sheet -Base). Berdasarkan hasil perhitungan didapatkan KAO sebesar 7,3% didapatkan nilai Stabilitas sebesar 925,00 kg, Flow sebesar 3,25 mm, Rongga Antar Agregat sebesar 23,48%, Rongga udara dalam Campuran sebesar 4,60%, Rongga Terisi Aspal sebesar 77,95%, Hasil Bagi Marshall sebesar 300,00 kg/mm.Kata Kunci : Hot Rolled Sheet - Base (HRS-Base), pasir zirkon, limbah kerikil, Parameter Marshall